Hubungan antara Grade Hipertensi dengan Tingkat Kemandirian Lansia dalam Activities Of Daily Living (ADLs) - Irma Darmawati; Febri Andri Kurniawan (Faletehan Health Journal, 2021)
The prevalence of hypertension in Indonesia has continued to increase. Decreasing the level of elderly independence due to hypertension is a major concern in achieving optimal quality of life. The purpose of this study was to determine the relationship between hypertension grade and independence level in activities of daily living. There were 49 participants selected by cluster sampling from elderly who diagnosed with hypertension. This research used a quantitative approach with cross sectional design. Analysis of the relationship between hypertension grade and elderly independence using Spearman rank correlation. The results showed that 55.1% of the elderly had grade II hypertension and 49% of the elderly had partial dependence. Based on correlation analysis, the results obtained p value 0.00 (<0.05) and r -0.56 with the conclusion that there is a fairly strong relationship between hypertension and independence of the elderly, with a negative direction means the higher blood pressure give a lower the elderly independence. Changes in the level of elderly independence caused by hypertension should be a concern for nurses to always monitor the grade of hypertension regularly every month. Family involvement is enhanced to provide family support that can help the elderly so that the quality of life of elderly hypertension can still be optimally achieved.